1997
DOI: 10.3109/01460869709026873
|View full text |Cite
|
Sign up to set email alerts
|

Breast-Feeding in the Workplace: How to Succeed

Abstract: As the numbers of women of childbearing age in the workforce continue to increase, some employers and employees have viewed maternal employment to be incompatible with breast-feeding. This qualitative study investigated factors that hindered as well as facilitated breast-feeding in the workplace. Findings suggest breast-feeding and employment can and should be compatible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 10 publications
1
20
0
Order By: Relevance
“…30 In addition, a qualitative study indicated that mothers reported that having child care near or at the workplace helped them to succeed at both working and breastfeeding. 31 Although we found that direct feeding of the infant was associated with longer duration of breastfeeding after return to work than pumping only, research on mothers who participate in work-site lactation programs and who only pump at work consistently has shown that they have long average duration of either breastfeeding or concurrent behavior. 19,22,23,32 This finding suggests that support for pumping at work can lead to breastfeeding outcomes similar to those of direct feeding.…”
Section: Discussionmentioning
confidence: 51%
“…30 In addition, a qualitative study indicated that mothers reported that having child care near or at the workplace helped them to succeed at both working and breastfeeding. 31 Although we found that direct feeding of the infant was associated with longer duration of breastfeeding after return to work than pumping only, research on mothers who participate in work-site lactation programs and who only pump at work consistently has shown that they have long average duration of either breastfeeding or concurrent behavior. 19,22,23,32 This finding suggests that support for pumping at work can lead to breastfeeding outcomes similar to those of direct feeding.…”
Section: Discussionmentioning
confidence: 51%
“…[6][7][8] Some of the most common problems experienced by employed breastfeeding mothers include increased fatigue, lack of time and a place at work to express breast milk, lack of support from employers, lack of refrigeration for milk storage, and difficulty maintaining an adequate milk supply. 7,[9][10] Further obstacles include lack of awareness and information regarding the benefits of breastfeeding on the part of health professionals, employers, families, and the public. 11 Women are able to identify the essential requirements for successful breastfeeding while working outside the home.…”
mentioning
confidence: 98%
“…Work place programmes that provide opportunities for mothers to take an extended maternity leave, perhaps on a part-time basis are positive determinants 41 . A work place that provides extended support over time, including facilities for expressing breast milk or even breastfeeding at work, can greatly increase the breastfeeding duration 68 . In some cultural contexts, the view of the breast as a sexual object can create problems for women who want to breastfeed their babies 69 .…”
Section: Community Attributesmentioning
confidence: 99%